GAMBARAN KELENGKAPAN RESEP PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT TEBET PERIODE JANUARI – MARET 2019 - Guruh Subagya; Vonny Nofrika; Widyanti Astuti (Jurnal Farmasi IKIFA, 2021)
The use of drugs is a therapeutic action that is very important in managing patients. Drug therapy usually manifests in the writing of a prescription as the final act of consulting the patient with the doctor after a doctor takes the history diagnosis and prognosis of the patient. In prescription writing, there are critical points that must be understood by both doctors and pharmacist. The failure of communication between and pharmacists one of the factors causing medication errors. The recipe must be clearly and completely written to avoid misperception between the two interpret a recipe. Recipe writing that is not according to the procedure and selection of drugs that are not right the treatment becomes ineffective and insecure, recurrence of the disease and the illness becomes prolonged. Pharmacist are responsible for carrying out prescription assessment activities in order to achieve optimal treatment and to minimize treatment failure, so that improve and guarantee drug service requirements. The study aims to description of the completeness of the outpatients prescription in pharmaceutical installation Tebet hospital period January to March 2019. This Scientific Writing is a type of quantitative descriptive research with secondary data retrieval of the outpatients prescription in pharmaceutical installation Tebet Hospital period january to march 2019. Percentage of completeness of outpatient prescriptions in pharmacy installation Tebet ospital period January- March 2019 as follows: doctor’s name 95,76 % or 791 prescriptions, SIP 94,92 % or 784 prescriptions, symbol R/ 97,82 % or 808 prescriptions, name of drugs and preparation 70,94 % or 586 prescription, drug dosage 74,94 % or 619 prescriptions, signatura 100 % or 826 prescriptions, initial the doctor 41,25 % or 343 prescriptions, and patient identity 65,86 % or 544 prescriptions.